(untitled) (Research, Society and Development, 2020)
The global market of dental implants is expecting to make USD 13.01 billion circulate by 2023 from USD 9.50 billion in 2018. The study of the materials to fabrication the implants has increased with the objective of extending the useful life of the material avoiding having to replace. Therefore, in this study we investigated the electrochemical behavior, wettability characterization and antimicrobial activity of titanium and the Ti-30Ta binary alloy. The titanium was cut into discs of 10 mm in diameter. The Ti-30Ta alloy was obtained from titanium and tantalum pure metals in a high purity argon atmosphere, homogenized in a vacuum at 1000ºC for 24 hours, cold -worked by a rotary swaging process and solubilized at 950 ºC for 2 hours followed by water cooling. Then, the bars were cut into discs. Corrosion resistance tests evaluated the electrochemical behavior, the wettability of the substrate surfaces was investigated using a sessile drop method and the biofilm formation was investigated by of S epidermidis. This study aims to investigate the corrosion resistance of Ti cp and the Ti-30Ta alloy at electrolyte solution NaCl 0,15M + NaF 0,03M and tested biofilm formation. From the results obtained, we concluded that the electrochemical behavior of both surfaces shows good resistance to corrosion solution and hydrophilic (< 90 °) behavior. However, the Ti-30Ta alloy decreases the adhesion of S epidermidis bacteria.